Growth, commodity prices, inflation and the distribution of income - Bloch, Harry (School of Economics and Finance, Curtin Business School, 2005)
Prebisch (1950) and Singer (1950) argue that the structure of the world economy leads to long-run deterioration in the net barter terms of trade for primary commodity producers in developing countries in their trade with manufacturers in industrialized countries. The ?Prebisch-Singer hypothesis? is based on the differential trading position of primary producers and manufacturers, especially the greater market power of manufacturers and unions representing industrial workers as compared to primary producers and their workers. This differential trading position gives rise to an increasing disparity in relative incomes favouring workers and firms engaged in manufacturing in the industrialized countries at the expense of workers and firms in primary production in developing countries.